Using Mixed Methods in Monitoring and Evaluation : Experiences from International Development - Bamberger, Michael (2012)
This paper provides an overview of the various ways in which mixing qualitative and quantitative methods could add value to monitoring and evaluating development projects. In particular it examines how qualitative methods could address some of the limitations of randomized trials and other quantitative impact evaluation methods; it also explores the importance of examining "process" in addition to "impact", distinguishing design from implementation failures, and the value of mixed methods in the real-time monitoring of projects. It concludes by suggesting topics for future research -- including the use of mixed methods in constructing counterfactuals, and in conducting reasonable evaluations within severe time and budget constraints.